2021
DOI: 10.1093/cid/ciab154
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Factors Associated With Coronavirus Disease 2019 Infection, Hospitalization, and Mortality Across Race and Ethnicity

Abstract: Background Data on the characteristics of COVID-19 patients disaggregated by race/ethnicity remain limited. We evaluated the sociodemographic and clinical characteristics of patients across racial/ethnic groups and assessed their associations with COVID-19 outcomes. Methods This retrospective cohort study examined 629,953 patients tested for SARS-CoV-2 in a large health system spanning California, Oregon, and Washington betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 14 publications
5
46
1
10
Order By: Relevance
“…Inequities in social determinants of health with downstream effects on overall health of racial/ethnic minority groups ( 34 ) likely also contributed to these disparities. Other studies have similarly found increased morbidity and mortality associated with COVID-19 among non-Hispanic Black ( 33 ) and Hispanic ( 35 , 36 ) persons compared with non-Hispanic White persons.…”
Section: Discussionmentioning
confidence: 85%
“…Inequities in social determinants of health with downstream effects on overall health of racial/ethnic minority groups ( 34 ) likely also contributed to these disparities. Other studies have similarly found increased morbidity and mortality associated with COVID-19 among non-Hispanic Black ( 33 ) and Hispanic ( 35 , 36 ) persons compared with non-Hispanic White persons.…”
Section: Discussionmentioning
confidence: 85%
“…Racial disparities have been noted in outcomes of COVID-19. 23 Hence, we included race as a covariate in our analysis. Testosterone, estradiol, and IGF-1 were measured at the time of presentation (ie, baseline or day 0) and at days 3, 7, 14, and 28 after admission (if the patient remained hospitalized).…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore critical to identify key modifiable risk factors that affect the case fatality of COVID-19. [4][5][6][7] Environmental factors, especially air pollution and temperature, have been widely identified to be associated with increasing risk of adverse health outcomes, such as for ischemic heart disease, stroke, diabetes, chronic obstructive pulmonary disease, and respiratory infection. [8][9][10][11] Emerging evidence indicates potential links between exposure to polluted air and COVID-19 mortality and fatality.…”
Section: Introductionmentioning
confidence: 99%